Accelerated myocardial fibrosis in young to middle-aged patients with hypertrophic cardiomyopathy - Shiro Nakamori; Ethan J. Rowin; Jennifer Rodriguez; Long H. Ngo; Warren J. Manning; Martin Maron; Reza Nezafat (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: The extent of late gadolinium enhancement (LGE) on cardiovascular magnetic resonance (CMR) in patients with hypertrophic cardiomyopathy (HCM) is associated with an increased risk of sudden cardiac death events. However, the clinical significance of age-specific longitudinal changes in LGE is not well characterized in HCM. We sought to assess whether the risk of LGE progression diverges between young to middle-aged (ages 20-59 years) and older (≥ 60) adults with HCM. Methods: A total of 102 HCM patients (age <60 years; n=75, age ≥60 years; n=27) undergoing serial CMR studies from two tertiary medical centers were evaluated. The median time interval between initial and follow-up CMR scans was 3.7 years. LGE was semiautomatically quantified by measuring regions with signal intensity >6 SD above the nulled remote myocardium and manually adjusting a grayscale threshold. Results: LGE was identified at baseline in 61 of the 102 HCM patients (60%), occupying 4.8 ± 3.9% of the left ventricular (LV) mass. At the end of the follow-up period, 53 of the 61 patients (87%) demonstrated an increase in the extent of LGE to 7.7 ± 5.4%, and 8 patients had no change. In 5 patients (5%), LGE increased to extensive with >15% of the LV mass. The rate of LGE progression was 0.7 ± 1.0%/year, including 21 patients (21%) with particularly accelerated progression of ≥1%/year. The risk of LGE progression ≥1%/year was significantly higher in patients <60 years than those ≥ 60 years (25% vs. 7%, p=0.03). The odds of LGE progression ≥1%/year was almost 4 times greater for patients <60 years compared with those ≥ 60 years (odds ratio, 4.2; 95%CI, 1.1-27.9). Age <60 years and LGE extent ≥ 10% were significant baseline predictors for future LGE progression ≥1%/year, even after adjustment for other potential risk factors. Conclusion: In HCM, progressive fibrosis occurs more frequently in young to middle-aged patients, underscoring the importance of repeating CMR to re-evaluate for potential LGE progression in this age group.